Net wealth across the euro area - why household structure matters and how to control for it - Pirmin Fessler; Peter Lindner; Esther Segalla (European Central Bank (ECB), 2014)
We study the link between household structure and cross country differences in the wealth distribution using a recently compiled data set for the euro area (HFCS). We estimate counterfactual distributions using non-parametric re-weighting to examine the extent to which differences in the unconditional distributions of wealth across euro area countries can be explained by differences in household structure. We find that imposing a common household structure has strong effects on both the full unconditional distributions as well as its mappings to different inequality measures. For the median 50% of the differences are explained for Austria, 15% for Germany, 25% for Italy, 14% for Spain and 38% for Malta. For others as Belgium, France, Greece, Luxembourg, Portugal, Slovenia and Slovakia household structure masks the differences to the euro area median and Finland and the Netherlands change their position from below to above the euro area median. The impact on the mean and percentile ratios is similarly strong and varies with regard to direction and level across countries and their distributions. We can confirm the finding of Bover (2010) that the effect on the Gini is somewhat less pronounced, but might mask relevant information by being a net effect of different accumulated effects along the distribution. Country rankings based on almost all of these measures are severely affected alluding to the need for cautious interpretation when dealing with such rankings. Furthermore, the explanatory power of household structure changes along the net wealth distribution. Therefore we argue for more flexible controls for household structure. We provide such a set of controls to account for household type fixed effects which are based on the number of household members as well as possible combinations of age categories and gender.
Keywords: D30; D31; 330; counterfactuals; household structure; non-parametric re-weighting; survey methodology; unconditional distribution; wealth distribution